MONITORING OF SEED COUNTER IN 1000 SEED WEIGHT TESTING - Milivojevic, Marija (Journal on Processing and Energy in Agriculture, 2022)
Accuracy and random selection of seeds when testing the 1000 seeds weight in the laboratory is of great importance in order to ensure the representativeness of the sample and precise information for further packaging process. The aim of this research was to check whether the laboratory seed counter selects seeds by shape and size and whether there is a trend during operation at maximum and reduced speed. Ten species of different seed sizes were used. Ten replicates of 100 seeds were counted by counter, the number of seeds was manually checked and the weight measured. The analysis of the obtained results showed that the counter is precise, but weight results showed selection of smaller seeds (Capsicum annuum and Glycine max) at maximum counting speed. Trend of larger seed selection was observed in Medicago sativa and pelleted Beta vulgaris. Slower counting (50% of the maximum speed), ensured precise counting without trends.